A new method to evaluate a corresponding colors dataset based on its two derived transforms. Issue 2 (3rd May 2016) - Cai, Shengyan; Chen, Qianwen; Wang, Haifeng
Abstract: Corresponding colors datasets are crucial in the study of chromatic adaptation transformations (CATs). A transform can be derived from a corresponding colors dataset. In this article, a second transform is derived by exchanging the two groups of tristimulus values of a dataset. Based on the two transforms a new method is proposed to evaluate a corresponding colors dataset. The evaluation criteria include the prediction difference between the two transforms and their prediction errors with visual results altogether. By the new method, nine superior datasets and four inferior datasets were picked from the 25 solo existing datasets. The research also included mixing different solo datasets and investigated their effectiveness. The results show that mixed datasets comprised of datasets with same illuminants and media have a certain value to derive CATs. Finally, 10 superior transforms derived in the experiment were compared with the four CATs recommended by the CIE. The results indicate that three of four CATs recommended by the CIE are superior to any sharpening transform derived in this experiment, but CIECAT94 is inferior to any one of them conversely. © 2016 Wiley Periodicals, Inc. Col Res Appl, 42, 150–155, 2017